Study On Encapsulation (Stabilization/Solidification) Of Waste Mercury Using Sodium Sulfide And Ordinary Portland Cement - Nik Asmadi Aznan, Nik Asmadi (2011)
This paper presents the study on encapsulation of waste mercury by using stabilization/ solidification method. Sulfide induced stabilization is used in this study and the stabilized mercury will be solidified with ordinary Portland cement. Two parameters that affect the stabilization/solidification process were investigated in order to enhance its effectiveness.